Emotionally focused therapy for couples and childhood sexual abuse survivors - MacIntosh, Heather B (University of Ottawa (Canada), 2005)
The purpose of this study was to explore the use of Emotionally Focused Therapy for Couples (EFT) with childhood sexual abuse survivors (CSA) and their partners. Ten couples participated in this exploratory study. In assessing outcomes the concept of the reliable change index was utilized to determine whether the treatment did have an impact on couples over the course of the therapy. Qualitative coding strategies were utilized to relate the process of change in couples to the identified outcomes. A case study replication methodology was utilized to examine the use of EFT with these couples thematically. Half of the couples in this study reported clinically significant increases in mean relationship satisfaction over the course of the therapy. Similarly, half of the CSA survivors reported clinically significant decreases in trauma symptoms on a self-report measure and a statistically significant decrease in trauma symptoms was identified on a standardized interview measure of trauma symptoms in the group of survivors. Very little change was identified over the course of therapy on a self-report measure of attachment. Thematic analyses identified numerous areas where trauma survivors were challenged in fully engaging in the therapy process. In particular, trauma symptoms such as affect dysregulation and hypervigilance, shame, anger, emotional numbing and dissociation were identified to play a role in the challenges that survivors experienced in fully engaging in the EFT therapy process. The EFT model and therapist behaviours were also analyzed observationally and results of these thematic analyses yielded clinical recommendations for working with CSA survivors and their partners in EFT for traumatized couples. Recommendations for future study were articulated.
Keywords: Psychology, Clinical.